Myths Revisited - O’Neill, G. Patrick (Canadian Journal of Higher Education, 1993)
Do universities reward teaching? Do universities reward publication? Which is rewarded more: teaching or publication? Do research and publication undermine good teaching? These questions, perhaps more than any others, spark emotional outbursts among academics. Many are quick to champion a view, but their arguments often fly in the face of hard data. What then do the data show? Are they exhaustive? Are they uniform? One set of answers is found in Professor Johnston's article entitled, "Myth Conceptions of Academic Work" which appeared in the Canadian Journal of Higher Education, Vol. XXI-2, 1991. Another set is found in this article. The reader is left to draw his or her own conclusion.